Komposisi Tubuh Domba Ekor Tipis yang Diberikan Pakan Bungkil Kedelai Terproteksi Tanin dengan Kadar Berbeda (THE BODY COMPOSITION OF THIN TAIL RAMSFED WITH PROTECTED TANNIN-SOYBEAN MEAL IN DIFFERENT LEVELS) - Salido, Wa Laili; Achmadi, Joelal; Purnomoadi, Agung (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
The aim of this study were to evaluate the effect of tannin concentration in protein protection ofsoybean meal and its influence on the change of body composition with urea space method (estimation)and cutting (direct). Sixteen male thin tail rams of eight month old with an average body weight of 11.81±1.65kg were used in this study. Treatment Groups of different tannin level were allotted according to a completelyrandomized design with four replicates for each treatment. The treatmen groups were T0 (complete feed +soybean meal not protected), T1 (complete feed + tannins protected soybean meal 0.5%), T2 (complete feed+ tannins protected soybean meal 1%), and T3 (complete feed + tannins protected soybean meal 1.5%).The treatment was performed in 10 weeks. However, In the week 0, fifth and tenth the rams body compositionwere measured with urea space technique. Result of the study showed that the feeding protected proteinwith different tannin levels did not significantly influence (P> 0.05) body composition of the samples. Theaverage content of body composition measured with the urea space method for body water, body proteinand body fat were 58.53%, 11.01%, and 20.74% respectively. Where as, the body composition measurementafter slaughtered for the body water, body protein and body fat were 3.08 kg, 0.50 kg and 0.89 kg respectively.The average increase of body protein and body fat that occurred during the 10-week study period were 0.37kg and 0.51 kg respectively. Based on these results it can be concluded that feeding protected proteincontained with tannin up to 1.5% may not be able to improve body composition of thin tail rams.
Keywords: protected protein; tannin; body composition